بناء اختبار تجهيز ومعالجة المعلومات للاعبي بعض الرياضات - المرسى، مني مختار; الشرقاوي، زهراء عبدالمنعم (جامعة حلوان - كلية التربية الرياضية للبنين, 2014)
يهدف البحث إلى بناء اختبار تجهيز ومعالجة المعلومات للاعبى بعض الرياضات لتحديد مستوى تجهيز ومعالجة المعلومات للاعبى بعض الرياضات من الجنسين، والتعرف على الفروق بين الجنسين فى هذا الاختبار، إتبعت الباحثتان المنهج الوصفى . تمثّل مجتمع البحث لاعبى أندية الدرجة الأولى والمستويات الرياضية العالية لبعض الرياضات الجماعية والفردية، وتم اختيار العينة بالطريقة العشوائية قوامها 104؛ 45 لاعب، 59 لاعبة أعمارهم تتراوح مابين 18 -22 سنة من عدة أندية، وكان قوام العينة الإستطلاعية 30 رياضى من الجنسين بغرض تقنين اختبار تجهيز ومعالجة المعلومات ومن داخل المجتمع الأصلى . وقد اظهرت النتائج تصميم اختبار تجهيز ومعالجة المعلومات للاعبى بعض الرياضات مكون من 24 عبارة موزعة على 3 محاور" المجال العقلى - المجال الوجدانى – المجال السلوكى "، و أسفرت النتائج عن مستوى مرتفع من تجهيز ومعالجة المعلومات للاعبين من الجنسين، كما وجدت فروق دالة احصائياً عند مستوى معنوية 0.05 فى محور " المجال الوجدانى " لاختبار تجهيز ومعالجة المعلومات بين اللاعبات واللاعبين لصالح اللاعبين، بينما لا يوجد فروق دالة احصائياً بين اللاعبين واللاعبات فى مجموع اختبار تجهيز ومعالجة المعلومات ومحوريه " المجال العقلى – المجال السلوكى . وقد أوصت الباحثتان بضرورة تطبيق اختبار تجهيز ومعالجة المعلومات والاستفادة منه فى دراسة الفروق فى مستوى تجهيز ومعالجة المعلومات بين الأنشطة الرياضية المختلفة. The purpose of this study was to construction test of equipping and processing information to determine the level of equipping and processing information for players in some sports of both gender, and to determine the differences between both gender in this test. Descriptive method was used, Research community represents players from first division clubs and sports high levels of some team and individual activities, The sample was selected randomly" players (n= 104) of both genders, male(n=45),female(n=59),Ages between 18-22 years from several clubs; pilot study was 30 playes of both gender from the same community to standardization the test of equipping and processing information . Results showed " desigh the test of equipping and processing information contained 3 factors " Mental – Emotional – Behavioral "; 24 phrases , and it showed a high level of equipping and processing information for players of both gender, differences at the 0.05 level of significance between male and female in emotional side in favor male players,but no differences at the 0.05 level of significance between male and female in total of the test of equipping and processing information and its factors" Mental – Behavioral ". Researchers recommend the need to apply the test of equipping and processing information and utilization to study the differences of equipping and processing information level between various sports .
Keywords: التمارين الرياضية -- التدريب الرياضي -- المهارات الرياضية